2017
DOI: 10.1149/2.0521709jes
|View full text |Cite
|
Sign up to set email alerts
|

Onset of Microbial Influenced Corrosion (MIC) in Stainless Steel Exposed to Mixed Species Biofilms from Equatorial Seawater

Abstract: 19The understanding of microbial influenced corrosion (MIC) in aerobic mixed biofilms 20 benefits from advanced microscopy and microbial ecology characterization of biofilms. Here, 21 the onset of MIC in stainless steel coupons was studied in both natural and artificial seawater. 22 Rapid selection of biofilm-forming microorganisms from natural seawater was observed for 23 field experiments. Potential ennoblement was observed only in natural seawater. A seawater 24 derived mixed microbial consortium enriche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…A study of aerobic copper corrosion revealed a lower charge transfer resistance in a biotic environment possibly due to breakdown of the passive film by microbiological action . Additionally, aerobic environments may undergo transformation into local anaerobic cells, due to the rapid microbiological growth which scavenges the oxygen . Aggressive pitting-type corrosion accelerated by the presence of aerobic P. aeruginosa biofilms has been found to accelerate corrosion of carbon, duplex, and 304 stainless steels. , …”
Section: Microorganisms and Chemical Microenvironment Of Mic Active S...mentioning
confidence: 99%
See 1 more Smart Citation
“…A study of aerobic copper corrosion revealed a lower charge transfer resistance in a biotic environment possibly due to breakdown of the passive film by microbiological action . Additionally, aerobic environments may undergo transformation into local anaerobic cells, due to the rapid microbiological growth which scavenges the oxygen . Aggressive pitting-type corrosion accelerated by the presence of aerobic P. aeruginosa biofilms has been found to accelerate corrosion of carbon, duplex, and 304 stainless steels. , …”
Section: Microorganisms and Chemical Microenvironment Of Mic Active S...mentioning
confidence: 99%
“…154 Additionally, aerobic environments may undergo transformation into local anaerobic cells, due to the rapid microbiological growth which scavenges the oxygen. 155 Aggressive pitting-type corrosion accelerated by the presence of aerobic P. aeruginosa biofilms has been found to accelerate corrosion of carbon, duplex, and 304 stainless steels. 65,156−158 Due to a large volume of bench scale investigation of MIC, the surface preparation of substrates is important for reproducibility of results, since the area of attachment of the bacteria can be influenced by the underlying microstructure.…”
Section: Microorganisms and Chemicalmentioning
confidence: 99%
“…The previous report has indicated that environmental pH has significant effect on the corrosion of materials not only in the abiotic environment [11][12][13][14][15], but also in the microbial environment [16][17][18]. However, the recent literature has focused mostly on MIC behaviour of duplex stainless steel at a neutral pH [19][20][21][22]. Corrosion on stainless steel caused by SRB in different pH environments has received less attention.…”
Section: Introductionmentioning
confidence: 99%
“…Sulfate-reducing bacteria (SRB) are the most ubiquitous microorganisms in anaerobic environments, and they are the most important microbes in MIC (microbiologically influenced corrosion) in the oil and gas systems which are mostly anaerobic and often involve seawater containing sulfate (Little and Lee, 2007;Sheng et al, 2007;Xu et al, 2016;Jia et al, 2017;Jogdeo et al, 2017). SRB MIC can induce mechanical degradations of metallic materials (Abedi et al, 2007;AlAbbas et al, 2013;Al-Nabulsi et al, 2015;Wu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%